Kematian Tuhan dalam Posmodernisme Barat: Studi Kritik Perspektif Ontologi Filsafat Islam: The Death of God in Western Postmodernism: A Critical Study from the Ontological Perspective of Islamic Philosophy - Ali Muchtar; M Zikri Tiftajani; Afkar Gilang Awantoro (Center of Islamic and Occidental Studies, 2026)
This article analyzes the concept of the death of God in Western postmodern philosophy from the ontological perspective of Islamic philosophy. By tracing the historical and philosophical roots of this idea from Nietzsche to postmodern thinkers such as Heidegger, Derrida, and Lyotard, the study argues that the death of God is a logical consequence of the reduction of theistic metaphysics within Western modernity. Employing a qualitative method through library research and critical-philosophical analysis of the major works of both Western and Islamic philosophers, this study examines the ontological assumptions underlying the postmodern critique of transcendence. The findings reveal that the concept of the death of God is not an ontological fact but rather an epistemological and historical phenomenon arising from the reduction of God to a metaphysical, moral, and cultural construct within the modern Western intellectual tradition. Drawing upon Ibn Sina’s concept of wājib al-wujūd, Mulla Sadra’s doctrines of aṣālat al-wujūd and tashkīk al-wujūd, as well as Syed Muhammad Naquib al-Attas’s Islamic worldview, the article argues that God is the Absolute Reality that transcends the categories of space, time, language, and social construction. Therefore, the claim concerning the death of God is understood as a crisis of knowledge and meaning rooted in epistemological secularization rather than a metaphysical reality. This article proposes a reconstruction of ontology grounded in tawḥīd as a philosophical alternative to postmodern nihilism and relativism, while also demonstrating the enduring relevance of Islamic metaphysics in addressing the contemporary crisis of meaning.